How to revive Illyricum? Political Institution of the "Illyrian Emperors" in the Early Modern Illyrism - Blažević, Zrinka (2011)
Early modern Illyrism might be described as a discursive product of the South Slavic branch of the Humanist res publica litteraria, which was during the 17th century intensively engaged in the symbolic constructing of Illyrian (trans)national identity. Intertextually and interdiscursively intertwined with the German Teutonism and Polish Sarmatism, early modern Illyrism represents both a discursive configuration of identity and a form of the symbolic political practice marked by high performative effects. As ideological product of the early modern absolutist political thinking, Illyrism can be interpreted as an utopian political platform aimed at constituting a supraregional state, culturally, ethnically and confessionally unified and homogenous, which was modelled on and legimized by the political tradition of the ancient Roman Empire. In order to express that link both semantically and symbolically, as well as to designate potential territorial scope of the new Empire which would rise from the ruins of the Ottoman one, ancient Roman administrative term Illyricum was discursively reactivated. At the time of its greatest magnitude the Roman province of Illyricum encompassed 17 smaller provinces, i.e. a whole range of territories from today’s Slovenia to the Aegean islands. Within the topological scheme of the early modern Illyrian discourse, a prominent status enjoyed a topos of “Illyrian rulers”. In the core of this topos is a fictive institutional tradition of “Illyrian Empire”, which begins with the so-called Illyrian Emperors (whose number oscillates between 25 and 60 in various “Illyrian” works). They once ruled Roman and Byzantine Empire and originated from the “Illyrian soil” (e.g. Diocletian, Constantine I). Besides endowing the national collectivity with respective political dignity, the main function of this discursively constructed translatio imperii is to attract contemporary political powers (e.g. Italian princes and Habsburg rulers) to liberate the people “who groan under the Turkish yoke” and as “legitimate successors of Illyrian rulers” revive once potent and glorious Illyricum Imperium.
Projekt MZOS
Projekt MZOS
ENG